2020
DOI: 10.3390/app10186273
|View full text |Cite
|
Sign up to set email alerts
|

Selected Physical and Mechanical Properties of Microwave Heat Treated Rubberwood (Hevea brasiliensis)

Abstract: The objectives of this study were to evaluate some of physical and mechanical properties of rubberwood (Hevea brasiliensis) as function of microwave heat treatment process. The specimens were heat treated at three temperature levels of 150 °C, 180 °C, and 220 °C for 20 min in a small microwave oven connected to a computer. Bending characteristics, namely modulus of elasticity (MOE), modulus of rupture (MOR) as well as hardness of the samples were tested. Dimensional stability in the form of swelling and water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Thus, the physical and mechanical properties of woods may diminish [33], which, in some situations, can be an advantage, as highlighted by Peres et al [46]. Terziev et al [33] explained that, in certain situations, MW treatment led to temperatures around 160 • C, in agreement with other studies [3,4]. Accordingly, the authors [33] intended to show the changes in micro-and ultrastructure levels of Norway spruce and radiata pine wood using two MW frequencies, 0.922 and 2.45 GHz.…”
Section: Speciessupporting
confidence: 52%
See 4 more Smart Citations
“…Thus, the physical and mechanical properties of woods may diminish [33], which, in some situations, can be an advantage, as highlighted by Peres et al [46]. Terziev et al [33] explained that, in certain situations, MW treatment led to temperatures around 160 • C, in agreement with other studies [3,4]. Accordingly, the authors [33] intended to show the changes in micro-and ultrastructure levels of Norway spruce and radiata pine wood using two MW frequencies, 0.922 and 2.45 GHz.…”
Section: Speciessupporting
confidence: 52%
“…Regarding the microstructural changes, it was observed that the cell walls were damaged, creating cracks on the samples. Lastly, the authors [4] stated that, compared to traditional approaches, 20 min MW treatment provided noticeable energy saving.…”
Section: Groupsmentioning
confidence: 99%
See 3 more Smart Citations